2011
DOI: 10.3346/jkms.2011.26.9.1140
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Knee Pain and Its Influence on Quality of Life and Physical Function in the Korean Elderly Population: A Community Based Cross-Sectional Study

Abstract: To investigate the prevalence of knee pain and its influence on physical function and quality of life (QOL), we examined 504 community residents of Chuncheon, aged ≥ 50 yr. Demographic information was obtained by questionnaire, and radiographic evaluations consisted of weight-bearing semi-flexed knee anteroposterior radiographs. Self-reported QOL and function were assessed using the Western Ontario and McMaster Universities Osteoarthritis (WOMAC) Index and Short Form 12 (SF-12). Performance-based lower extremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 25 publications
(31 reference statements)
6
44
1
5
Order By: Relevance
“…In adults, physical approaches have been shown to decrease the likelihood of declines in health-related QoL, 27 thus they may similarly benefit those with frequent UKP or BKP specifically. 24 The incorporation of more physical activity into the lifestyles of adults with knee pain led to improvements in the physical domain of health-related QoL relative to adults with knee pain who is less physically active. 1 Clinical trials of physical exercise programs and cross-sectional studies of community-dwelling adults have shown that greater physical activity is associated with better long-term health-related QoL in the adult population.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, physical approaches have been shown to decrease the likelihood of declines in health-related QoL, 27 thus they may similarly benefit those with frequent UKP or BKP specifically. 24 The incorporation of more physical activity into the lifestyles of adults with knee pain led to improvements in the physical domain of health-related QoL relative to adults with knee pain who is less physically active. 1 Clinical trials of physical exercise programs and cross-sectional studies of community-dwelling adults have shown that greater physical activity is associated with better long-term health-related QoL in the adult population.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, individuals with knee pain performed poorly on the repeated CST and a test of usual walking [ 21 ]. It is well understood that knee pain is a factor in reduced knee extensor strength in individuals with OA [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It increases the risks of morbidity because of loss of functional capacity, including difficulty in walking, inability to perform self-care, transferring, and going up and down stairs. Knee OA not only impairs physical functions but also reduces quality of life 2. In addition, it is the third leading cause of life-years lost due to disability 3…”
Section: Introductionmentioning
confidence: 99%